Importance of Basel III Norms in Digital banking - Gupta, H (International Journal of Computer Sciences and Engineering, 2025)
The researcher has studied the views of people in respect of benefits of cashless transaction if transactions are safe, secure and risk free. The data was collected from the respondents with the help of structured questionnaire administered in Mumbai Region and analysed using simple percentage method, Mean, Median, Mode and One Sample Test with an objective to identify the benefits of digital banking specifically in respect of cashless transaction and to ascertain the operational risk associated with it. The study will also ponder upon on how Indian banks can promote digital banking by focusing on cashless transactions and through mitigate operational risk with proper implementation of Basel III norms. The study will also evolve on how Basel III norms are important for booming digital banking and smooth functioning of cashless transactions if highly automated technology is properly controlled from all types of risks including strengthening of internet security.